PERKEMBANGAN ILMU USHUL FIQH PASCA IMAM MADZHAB HINGGA ABAD MODERN (Kajian Terhadap Metode Ijtihad dan Penerapannya) - Abdul Muthalib (Sekolah Tinggi Agama Islam Sumatera Medan, 2019)
The purpose of this writing is to describe the description of the activities of ijtihad of the mujtahids in the post-Imams era and also in the modern era in solving problems that arose in that era. The method used in this paper is the literature study method. The results of the study indicate that, the period after the Imam's school of worship is called the taqlid, jumud or vacuum period. However, this does not mean that the activities of ijtihad were stopped altogether. At this time the activities of ijtihad can be seen from the gathering of the ideas of Islamic scholars, comparing the opinions of the Imams of madzahb to take the opinion that is considered the most powerful, formulating the basis of the footing and methods of ushuliyah which form the basis of ijtihad and fatwa of the Imams of the school of thought, both in the form of sharia (( شرح , hasyiah ( حشيه ) or in the form of khulashah. The revival or modern era began around 1800 AD. In this period, Islamic thinkers tried to reconstruct the ushul fiqh methodology that had previously been built by the Imam of the school of thought) The reason is that the methods of the Imam of the school are less relevant in answering the problems that arise, given the increasingly complex problems.